Interconnectedness of trust-commitment-export performance dimensions: A model of the contingent effect of calculative commitment - AFM Jalal Ahamed; Fabrizio Noboa (Cogent Business & Management, 2022)
This research on relationship marketing aims to revisit and reposition different foci of trust, commitment, and performance perception in the export/import relationships and explore the interconnectedness effects. We have collected self-reported survey questionnaire responses from 142 non-oil exporters in Ecuador. The data were analyzed with SmartlPls 3.0 software. We found that calculative commitment negatively moderates inter-organizational trust and affective commitment relationships. The other significant findings include the indirect relationship (mediating effect) of affective commitment to financial export performance through relationship export performance. With these novel contributions, we also identify some expected relationships- as both interpersonal and inter-organizational trust positively affects affective commitment, and relationship export performance significantly predicts financial export performance. Cross-sectional data collection and responses from one side of the export-import dyad are one of this research's limitations. However, they are not uncommon in export marketing literature. Giving a justified position of different dimensions of trust and commitment in the export-import equation is the novelty of this scholarship. Clarifying the affective commitment and export performance relationship is another contribution of this research. Nevertheless, the dimensional views of trust and commitment re-established some known assumptions in a less researched country setting should also be considered a contribution.
Keywords: 650; affective commitment; calculative commitment; inter-organizational trust; Interpersonal trust; Latin America